A Study on Wealth Management During Crisis : An Empirical Study Using Downside Risk Approach in India - Kumari, Divya; Parikh, Abhishek (Indian Journal of Research in Capital Markets, 2023)
Purpose : The present study identified the factors influencing shareholders’ wealth during a crisis like COVID-19. The growing importance of the capital asset pricing model (CAPM) in shareholders’ minds leads to identifying new important factors that ruin wealth during a downturn. Hence, the present study is a humble attempt to find such a factor identified as downside beta. Methodology : The main independent factor, namely market risk premium, is very popular as CAPM of equity returns. The importance of protecting wealth becomes more important than creating wealth. This leads to considering only downside market movement to understand equity returns in the current study. Furthermore, a proposed model was introduced as Downside CAPM (D-CAPM). D-CAPM structural changes were captured during COVID-19 by taking data from April 1, 2019 â€“ March 31, 2020, and April 1, 2020 â€“ March 31, 2021. Findings : We found that the slope of the relationship relatively showed more sensitivity to downside movement. However, individual stocks’ slope of relationship improved after COVID-19. It showed improved return sensitivity after the COVID-19 scenario, even when the market turned negative. Practical Implications : The outcome of this study will aid investors, investment advisors, portfolio managers, and others in protecting and managing their wealth even during a crisis using the DCAPM method. Originality : Unlike prior research on D-CAPM, this study attempts to capture structural changes in the model during COVID-19 in India.